2016
DOI: 10.2337/dc15-1817
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and the Association of Postoperative Hyperglycemia With Clinical and Economic Outcomes in Cardiac Surgery

Abstract: OBJECTIVEThe management of postoperative hyperglycemia is controversial and generally does not take into account pre-existing diabetes. We analyzed clinical and economic outcomes associated with postoperative hyperglycemia in cardiac surgery patients, stratifying by diabetes status.RESEARCH DESIGN AND METHODSMulticenter cohort study in 4,316 cardiac surgery patients operated on in 2010. Glucose was measured at 6-h intervals for 48 h postoperatively. Outcomes included cost, hospital length of stay (LOS), cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 39 publications
3
40
0
2
Order By: Relevance
“…Apart from the different diabetes treatment, the opposite relationship between glycemia and outcome in the current study of Greco could be explained by a difference in preadmission glucose levels. Indeed, the HbA1c was significantly different between insulin-treated and non-insulin-treated diabetics, with a significantly higher HbA1c (or higher mean glucose levels) in insulin-treated diabetics (17).…”
Section: Editorialmentioning
confidence: 94%
See 3 more Smart Citations
“…Apart from the different diabetes treatment, the opposite relationship between glycemia and outcome in the current study of Greco could be explained by a difference in preadmission glucose levels. Indeed, the HbA1c was significantly different between insulin-treated and non-insulin-treated diabetics, with a significantly higher HbA1c (or higher mean glucose levels) in insulin-treated diabetics (17).…”
Section: Editorialmentioning
confidence: 94%
“…In addition, if hyperglycemia would be advantageous in insulin-treated diabetics, one would expect that patients with at least two hyperglycemic measurements would perform better than patients with only one measurement in that range, which was apparently not the case. It is also unclear why the authors did not always correct for all baseline risk factors (17).…”
Section: Editorialmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that anaemia is more prevalent than other surgeries in cardiac surgery (24). Another problem following CABG is hyperglycaemia which is related to decreased operational outcomes in the long run and increased mortality and morbidity after CABG (25,26). Hyperglycaemia after CABG has been observed in the non-diabetic patients (27).…”
Section: Introductionmentioning
confidence: 99%